Collective Resources and Violent Crime Reconsidered: New Orleans Before and After Hurricane Katrina. Issue 13 (July 2021) - Weil, Frederick D.; Barton, Michael; Rackin, Heather; Valasik, Matthew; Maddox, David
Social research has long argued that collective resources and major events like disasters have an important impact on violent crime, but it has been difficult to show their effects because data are scarce. We conducted a large survey in New Orleans after Hurricane Katrina that included questions about collective resources. We aggregated our sample to the census tract level and merged it with data on concentrated disadvantage and violent crime. Our analyses show that bridging social networks are associated with lower levels of violent crime, while bonding social networks are associated with higher levels. Social trust is associated with lower levels of violent crime, but civic engagement has no impact. Concentrated disadvantage is associated with higher levels of violent crime. Finally, our results suggest that disaster recovery increased the importance of collective resources but not concentrated disadvantage on violent crime.